Farmer's choice - Mlali RISING - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
This video highlights how through Africa RISING program interventions, a group of farmers at Mlali Village in central Tanzania are today making choices that will ensure they improve their livelihoods while conserving the natural resource base for the future generations. Africa RISING (https://africa-rising.net) is supported by USAID as part of the US Government’s Feed the Future initiative. Work with smallholder farmer communities is being implemented in six countries – Tanzania, Malawi, Zambia, Ethiopia, Mali and Ghana.